Gambaran Perbedaan Pola Asuh terhadap Tingkat Adiksi Smartphone pada Remaja Awal Kota Bukittinggi - Fadila Lailatul Isttianah; Rida Yanna Primanita (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
The use of smartphones in children needs assistance, supervision, and open communication from parents so as not to have a negative impact. Parenting plays an important role in shaping children's behavior towards smartphone use. This study aims to determine the parenting style applied by parents and its relationship with the level of smartphone addiction in early adolescents. The subjects in this study amounted to 14 junior high school students in Bukittinggi City who were selected using purposive sampling technique. This study used a quantitative approach with a questionnaire instrument. The results of the study show that the parenting style that is most widely applied is democratic parenting style. It was found that 5 subjects were in the high addiction category, 3 subjects in the medium addiction category, and 2 subjects in the low addiction category. However, no significant difference was found between the type of parenting and the level of smartphone addiction in early adolescents in Bukittinggi City. Further research is recommended to involve a larger number of subjects so that the results obtained are more objective and general.